Malpraktek dan Hadis Nabi: Menggali Pesan Kemanusian Nabi Muhammad saw. dalam Bidang Medis - Benny Afwadzi; Nur Alifah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Malpractice is a humanity phenomenon that has attracted publics attention today. For example, from 2006-2012 there were 182 malpractice cases with various types of negligence. This huge amount is certainly very worrying. Meanwhile on the other hand, the question might arise, did the Prophet Muhammad saw. through hadith ever speak of this phenomenon? If yes, what are the humanity messages contained in these hadiths? This article is written to describe malpractice in the view of hadith. According to the data from hadith collection, both canonic and non-canonic, and combined with interpretatif method, the article concluded that the Prophet Muhammad saw. had discussed the prohibition of malpractice through the hadith narrated by Ab? D?wud and other mukharrij. Indeed, there are at least four messages contained in the hadiths, namely first, the necessity for a Muslim to respect the lives of others, because life is not something cheap in price. Second, in addressing the problem of humanity, even more so in the field of medicine should be done with in a professional manner. Third, the command to always humanize the human while still promoting the spirit of religion (humanitarianism). Fourth, giving a sense of justice to humanitarian system